2008
DOI: 10.1002/ctpp.200810087
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Magnetic Mirror on Near Wall Conductivity in Hall Thrusters

Abstract: The effect of magnetic mirror on near wall conductivity is studied in the acceleration region of Hall thrusters. The electron dynamics process in the plasma is described by test particle method, in which electrons are randomly emitted from the centerline towards the inner wall of the channel. It is found that the effective collision coefficient, i.e. the rate of electrons colliding with the wall, changes dramatically with the magnetic mirror effect being considered; and that it decreases further with the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…5(c), it can also be found that the plasma density near the inner wall is smaller compared with that near the outer wall in acceleration region. It is caused by the magnetic mirror effect, which has been confirmed by our former works [22].…”
Section: Various Parameters Distribution At Different Momentssupporting
confidence: 73%
“…5(c), it can also be found that the plasma density near the inner wall is smaller compared with that near the outer wall in acceleration region. It is caused by the magnetic mirror effect, which has been confirmed by our former works [22].…”
Section: Various Parameters Distribution At Different Momentssupporting
confidence: 73%
“…Their results also showed that a high magn etic mirror ratio improves the concavity of potential profiles, which leads to stronger ion focus in the exhaust area. Yu et al [11] studied the magnetic mirror effect on electron transport using the test particle method. They found that the asymmetry of radial electron mobility is reinforced in the presence of a magnetic mirror.…”
Section: Introductionmentioning
confidence: 99%